Parthenolide: pioneering new frontiers in hematological malignancies - Elmira Zarei; Ayda Zarei; Azadeh Omidkhoda (Frontiers in Pharmacology)
Hematological malignancies are the fifth most prevalent cancer category in developed countries, presenting significant treatment challenges. The side effects of chemotherapy and its non-selective nature have led researchers to explore combination therapies to enhance efficacy and improve patient outcomes. Parthenolide (PTL) emerges as a promising candidate, being the first small molecule identified for its selective action against leukemic stem cells. This article provides an overview of PTL’s effects and its potential as a complementary treatment for hematological malignancies. A systematic search in PubMed, Scopus, Embase and Web of Science identified relevant studies using keywords and MeSH terms. Peer-reviewed studies examining PTL’s mechanisms and therapeutic potential were included, while non-hematological studies and those lacking rigor were excluded. PTL targets key signaling pathways to combat malignancy, inhibiting NF-κB and signal transducer and STAT3, promoting ROS production, and activating p53. These mechanisms contribute to its effectiveness in treating hematological malignancies. Approaches incorporating PTL or its derivatives show promise in increasing leukemic cell sensitivity to existing therapies and reducing resistance likelihood. Additionally, studies indicate that other drugs can synergistically enhance PTL’s ability to eliminate leukemic cells. In conclusion, PTL represents a promising avenue for improving therapeutic outcomes in hematological malignancies, warranting further investigation into its mechanisms and potential in combination therapies.